Race and Gender Differences in the Use of Direct Acting Antiviral Agents for Hepatitis C Virus. (30th April 2016) - Kanwal, Fasiha; Kramer, Jennifer R.; El-Serag, Hashem B.; Frayne, Susan; Clark, Jack; Cao, Yumei; Taylor, Thomas; Smith, Donna; White, Donna; Asch, Steven M.
Abstract : In a large cohort of patients with hepatitis C virus (HCV) infection, this study found that black patients and younger women were less likely to receive the new direct acting antiviral agents than the comparison groups. Abstract : Background. Direct acting antiviral agents (DAA) are highly effective yet expensive. Disparities by race and/or gender often exist in the use of costly medical advances as they become available. Methods. We examined a cohort of hepatitis C virus (HCV) patients who received care at the Veterans Administration facilities nationwide. We evaluated the effect of race and gender on DAA receipt after adjusting for socioeconomic status, liver disease severity, comorbidity, and propensity for healthcare use. To determine if disparities had changed over time, we conducted a similar analysis of HCV patients who were seen in the previous standard of care treatment era. Results. Of the 145 596 patients seen in the current DAA era, 17 791 (10.2%) received treatment during the first 16 months of DAA approval. Black patients had 21% lower odds of receiving DAA than whites (odds ratio [OR] = 0.79; 95% confidence interval [CI], .75, .84). Overall, women were as likely to receive treatment as men (OR = 0.99; 95% CI, .90–1.09). However, the odds of receiving DAAs were 29% lower for younger women compared with younger men (OR = 0.71, 95% CI, .54–.93). Similar to the DAA cohort, black patients had significantly lower odds of receiving treatment than whites (OR = 0.74, 95% CI, .69–.79) in the previous treatment era. The racial difference between the 2 eras did not reach statistical significance. Conclusions. There were unexplained differences among HCV population subgroups in the receipt of new DAA treatment. Targeted interventions are needed for black patients and younger women.